Osteoradionecrosis of the mandible: Etiology, prevention, diagnosis and treatment - Rayatt Sukh; Mureau Marc; Hofer Stefan (Indian Journal of Plastic Surgery)
The treatment of head and neck cancer remains a challenge. Despite advances in surgical reconstructive techniques, most patients will require adjuvant therapy in the form of radiotherapy or chemo-radiotherapy to improve locoregional control. The short- and long term side effects of radiotherapy can be difficult to treat. In this review the causative effects and pathogenesis of osteoradionecrosis of the mandible will be highlighted. In addition, preventive measures and clinical features of radiotherapy induced damage will be presented. Finally, medical and surgical management of osteoradionecrosis, as well as, reconstructive surgery of the mandible will be discussed. At the end of this paper the reader should have up to date knowledge concerning the etiology, prevention, diagnosis and treatment of patients with osteoradionecrosis of the mandible.